Cutting Down on Post harvest Losses - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
To meet the growing food needs of developing countries, there has been increasing pressure to improve yields in indigenous agriculture. In many places, this has been achieved through the use of higher-yield crops, better irrigation, larger...